Análisis de contenido de la información de El Comercio y El Telégrafo sobre el caso Chevron-Texaco en Ecuador - Cevallos Hidalgo, Ana Katherine (2015)
The enforcement of a content analysis of journalistic information given about the situation generated by the case Chevron-Texaco in Ecuador, since March to May 2014, is of great importance, trying to prove whether press of Ecuador has a position marked in favor, against or neutral in terms of the content, the space given to the notice and the form representing a story, where the main stakeholders are: the president of Ecuador, Rafael Correa, and the oil company Chevron-Texaco.